How error classification systems can impact on incident reporting and analysis - Taib, Ibrahim Adham; Caponecchia, Carlo (2014)
Backgrounds: Incident reporting systems often play a critical role in how high-risk organizations such as aviation, healthcare, and nuclear power generation understand and therefore manage incidents. Integral to the effectiveness of incident reporting systems are reliable and useful error classification systems. Results: In this paper, we dis-cuss how error classification systems can influence the information that is extracted from medical error reports, particularly information pertaining systemic factors of patient safety incidents. We also explain the importance of terminology in designing a reliable and easy to use error classification system.